THE STUDY OF INTERACTION OF p-OXYACETOPHENONE WITH CARBONIC ACIDS HYDRAZIDES (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The interaction between p-oxyacetophenone and a number of carbonic acids hydrazides gives corresponding alkyl (cyanoalkyl) carbonylhydrazones. The possibility of ring-chain tautomerism in obtained systems has been studied.
Keywords: alkyl carbonylhydrazones; p-oxyacetophenone; carbonic acids hydrazides